2020
DOI: 10.1111/bcp.14504
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term trajectories of medicine use among older adults experiencing polypharmacy in Australia

Abstract: Aims To explore longitudinal changes in the number and type of medicines used among older people who experience polypharmacy. Methods We used pharmaceutical claims for a 10% sample of Australian Pharmaceutical Benefits Scheme beneficiaries to identify people aged 70 years and older who were exposed to 5 or more medicines on 15 February 2014. Using group‐based trajectory modelling, we explored changes in the quarterly number and type of medicines used over a 5‐year period (2014–2018). Results In our cohort of 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Our findings confirm that polypharmacy is common among older patients and increases over time, as reported in various studies [9,10,[29][30][31][32][33]. Age is an important factor driving the development of polypharmacy and the accumulation of chronic health conditions accelerates the use of multiple drugs.…”
Section: Plos Onesupporting
confidence: 91%
“…Our findings confirm that polypharmacy is common among older patients and increases over time, as reported in various studies [9,10,[29][30][31][32][33]. Age is an important factor driving the development of polypharmacy and the accumulation of chronic health conditions accelerates the use of multiple drugs.…”
Section: Plos Onesupporting
confidence: 91%
“…A review by Sirois and colleagues reported that more than 46 definitions of polypharmacy were retrieved from the literature [58]. Clearly, this makes exploring the prevalence of polypharmacy difficult and is one reason why such a range in prevalence has been reported [59•, 60••, [61][62][63].…”
Section: Prescribing In the Face Of Multimorbiditymentioning
confidence: 99%
“…Multimorbidity is common in older adults leading to the concurrent use of multiple medications or polypharmacy [ 1 , 2 ]. Polypharmacy is commonly defined as the use of five or more regular medications [ 3 5 ] and is inherently dynamic depending on the health status of the patient [ 4 ]. A recent study in Australia found that the most commonly used types of medications in older adults with polypharmacy were medications for the cardiovascular system followed by alimentary tract and metabolism, and the nervous system [ 4 ].…”
Section: Introductionmentioning
confidence: 99%